2016
DOI: 10.1200/jco.2015.63.4550
|View full text |Cite
|
Sign up to set email alerts
|

CELF4Variant and Anthracycline-Related Cardiomyopathy: A Children’s Oncology Group Genome-Wide Association Study

Abstract: We report a modifying effect of a polymorphism of CELF4 (rs1786814) on the dose-dependent association between anthracyclines and cardiomyopathy, which possibly occurs through a pathway that involves the expression of abnormally spliced TNNT2 variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 34 publications
0
103
0
2
Order By: Relevance
“…Five studies included both children and adults in their report 3639, 44 . Nineteen studies described the ethnicity of their participants 20, 23, 3040, 43–45, 47, 50, 51 but, there were inconsistencies in reporting of race/ethnicity. For example, Weiss et al 33 described their participants either as Caucasian or not while Blanco et al 34 described their participants as White, Black and others.
Figure 1PRISMA flow diagram showing the selection process and criteria of the included studies.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies included both children and adults in their report 3639, 44 . Nineteen studies described the ethnicity of their participants 20, 23, 3040, 43–45, 47, 50, 51 but, there were inconsistencies in reporting of race/ethnicity. For example, Weiss et al 33 described their participants either as Caucasian or not while Blanco et al 34 described their participants as White, Black and others.
Figure 1PRISMA flow diagram showing the selection process and criteria of the included studies.
…”
Section: Resultsmentioning
confidence: 99%
“…Most studies using subjective outcomes defined cardiotoxicity as the presence of signs and symptoms requiring intervention 2123, 30, 31, 33, 3537, 41, 4749 . In addition, some studies have used the left ventricular ejection fraction (LVEF) or shortening fraction (SF) as an objective measure, but the cut-off points varies.…”
Section: Resultsmentioning
confidence: 99%
“…Among the most extensively studied long‐term outcomes to date is anthracycline‐induced cardiotoxicity. Genes in which polymorphisms have been associated with cardiomyopathy and/or congestive heart failure include, but are not limited to, solute carrier family 2 member 3 ( SLC2A3) , ATP binding cassette (ABC) subfamily B member 1 ( ABCB1 ), ABCB4 , and ABCC1 , which are involved in drug transport; carbonyl reductase 3 ( CBR3 ), which is associated with the 2‐electron reduction of anthracyclines, a main route of anthracycline metabolism; CUGBP Elav‐like family member 4 ( CELF4 ), a regulator of alternate protein splicing, including cardiac troponin; and hyaluronan synthase 3 ( HAS3 ) and neutrophil cytosolic factor 4 ( NCF4 ), both of which are implicated in defense against reactive oxygen species . Similarly, studies among ALL survivors have indicated that polymorphisms in genes likely to affect the action of antileukemia medications, such as vitamin D receptor ( VDR ) and thymidylate synthetase ( TYMS ), are associated with osteonecrosis, while corticotropin‐releasing hormone receptor 1 ( CRHR1 ) polymorphisms alter the risk of bone density deficits .…”
Section: Geneticsmentioning
confidence: 99%
“…Ten cohort studies reported cardiotoxicity outcomes across Europe and North America (Table 3). 3,[31][32][33][34][35][36][37][38][39] Two studies incorporated the ATP binding cassette subfamily C member (ABCC) family, with a risk associated with rs7627754, 31 rs3743527 TT genotype and in combination with the rs246221 TC/TT genotype. 34 Blanco et al found the expression of carbonyl reductase 3 (CBR3) was associated with cardiotoxicity, 36 whilst no association was found in the authors' previous study.…”
Section: Cardiotoxicitymentioning
confidence: 99%